Formulation of chitosan-based nanoparticles for delivery of proteins and peptides - Vellore Janarthanan, Mohanraj (Curtin University, 2003)
Delivery of complex molecules such as peptides, proteins, oligonucleotides and plasmids is an intensively studied subject, which has attracted considerable medical and pharmaceutical interest. Encapsulation of these molecules with biodegradable polymers represents one way of overcoming various problems associated with the conventional delivery of macromolecules, for example instability and short biological half-life. The use of carriers made of hydrophilic polysaccharides such as chitosan, has been pursued as a promising alternative for improving the transport of biologically active macromolecules across biological surfaces. The development of nanoparticles as a delivery system also has major advantages of achieving possible drug protection, controlled release and drug targeting by either a passive or an active means. The aim of this study was to develop a simple and effective method to formulate biodegradable nanoparticles for the delivery of a model protein-bovine serum albumin (BSA) and an angiogenesis inhibitor, arginine-rich hexapeptide (ARE peptide). Major factors which determine nanoparticle formation and loading of the protein and the peptide as well as the underlying mechanisms controlling their incorporation and release characteristics were investigated. The preparation technique, based on the complex coacervation process, is extremely mild and involves the mixture of two aqueous solutions (chitosan and dextran sulfate) at room temperature. The formation of nanoparticles is dependent on the concentrations of chitosan (CS) and dextran sulfate (DS); particles with size, of 257 to 494nm can be obtained with 0.1%w/v solutions of CS and DS. Zeta potential of nanoparicles can be modulated conveniently from -34.3mV to +52.7mV by varying the composition of the two ionic polymers.Both bovine BSA and the ARH peptide were successfully incorporated into CS-based nanoparticles, mainly via an electrostatic interaction, with entrapment efficiency up to 100% and 75.9% for the protein and peptide respectively. Incorporation of both the protein and peptide into nanoparticles resulted in an increase in size suggesting their close association with the nanoparticle matrix material. The difference in sign and magnitude of zeta potential of empty and macromolecules-loaded nanoparticles supports the hypothesis that protein and peptide association with nanoparticles can be modulated by their ionic interaction with the oppositely charged ionic polymer (DS) in the nanoparticles. The release of BSA from the nanoparticles was very slow in water compared to that in l0mM phosphate buffer pH 7.4; whereas, ARH peptide showed extremely low level of release in water at the low ratio of DS but at the high ratio of DS, its release was in biphasic fashion, with an initial burst effect followed by an almost constant but very slow release up to 7 days in both water and 1 OmM phosphate buffer (pH 7.4). It was found that, unlike ARH peptide, the percentage of BSA released was relatively slower for the nanoparticles with a high ratio of DS. It is speculated that this difference in the release behaviour of BSA and ARH peptide, could be due to the effect of molecular size of the compounds and their interaction with the polymer matrix of the nanoparticle. The results of this study suggest that these novel CS/DS nanoparticulate system, prepared by a very mild ionic crosslinking technique, have potential to be a suitable carrier for the entrapment and controlled release of peptides and proteins.